2014
DOI: 10.1007/s00270-014-0921-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Flow Redistribution in Patients Treated with Radioembolization

Abstract: All embolization procedures were performed successfully with no complications, and the flow redistribution was obtained in all cases. Results in term of toxicity, median dose administered, and radiological response were comparable with standard radioembolizations. Our findings confirmed the intratumoral flow redistribution after embolizing the accessory arteries, which makes it possible to treat the tumour through its single main feeding artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Furthermore, it was shown that redistribution of hepatic blood flow by means of embolizing certain hepatic arteries is not always successful. This method is commonly applied in RE and other interventions such as trans-arterial chemoembolization, to simplify procedures and to reduce risk of complications [8,9]. Case #4 was one of several cases in which this redistribution was not evident on posttreatment imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that redistribution of hepatic blood flow by means of embolizing certain hepatic arteries is not always successful. This method is commonly applied in RE and other interventions such as trans-arterial chemoembolization, to simplify procedures and to reduce risk of complications [8,9]. Case #4 was one of several cases in which this redistribution was not evident on posttreatment imaging.…”
Section: Discussionmentioning
confidence: 99%
“…An innovative approach to dealing with coil migration into the vascular distribution of prospective 90 Y RE is intrahepatic vascular flow redistribution, a strategy used to consolidate arterial flow to tumors by embolizing accessory feeders to allow single vessel 90 Y RE. 13,14 In this scenario, complete occlusion of the branch vessel into which coil migration occurred may be used to develop collateral blood supply from other intrahepatic arteries to allow 90 Y administration (►Fig. 14); while not an ideal circumstance, this approach may be the most successful in some patients.…”
Section: Embolization Techniquementioning
confidence: 99%
“…Dosimetry information is summarized in Table 2. Required 90 Y glass microsphere activity (TheraSphere ® ; BTG International, West Conshohocken, PA) was determined based on the target liver absorbed dose of 90-120 Gy, the volume of the liver tissue to be treated, and LSF using standard methodology (26). For the purpose of dose calculations, residual activity in the treatment vial was assumed to be 1%.…”
Section: Dosimetry and Treatmentmentioning
confidence: 99%
“…Vessels targeted for protective embolization and lung shunt study results are summarized in Table 2. Hepatic arterial flow consolidation (25,26) was attempted in three patients by embolizing accessory right or left hepatic artery branches. Lung shunt fraction (LSF) was calculated on the basis of planar images using standard methodology (26).…”
Section: Patient Evaluationmentioning
confidence: 99%
See 1 more Smart Citation